The Myth of the Danaids in its sources: Translation and notes - Mota, Marcus (Revista Archai, 2024)
The myth of the Danaids is recorded with variations in various poetic and non-poetic texts from Classical Antiquity. This paper collects and translates the main texts that help build the myth's reception in its attempts to construct a saga for female figures and their ambivalences.